Regulatory T cells in skin homeostasis and inflammation - Adelmann, K (2015)
Regulatory T cells (Tregs) are crucial controllers of inflammation. Patients with a genetic defect in the lineage defining transcription factor Foxp3 suffer from a broad spectrum of autoimmune diseases, including early manifestation of various types of skin inflammation. However, our knowledge about the properties of skin resident regulatory T cells under homeostatic and pathologic conditions and in particular in inflammatory diseases of the skin such as psoriasis is limited. In order to address this open question, phenotypic characterization and transcriptomic analyses of murine skin Tregs were performed. The majority of CD4+ T cells in homeostatic skin express the transcription factor Foxp3. These Tregs show a unique profile, are mainly thymic derived nTregs and are enriched in markers associated with a highly suppressive phenotype such as CD25, CD103, IL-10, ST2, and GATA-3. To delineate the role of Tregs in psoriasis-like inflammation, the imiquimod model of psoriasiform inflammation was used. Tregs are significantly increased during skin inflammation and retain their suppressive phenotype and trancriptome. Treg depletion before and during imiquimod treatment led to exacerbated inflammation and dense leukocytic infiltrate in the dermis and epidermis. Furthermore, the exacerbated inflammation was characterized by a significant increase in IL-12 and infiltration of IFN- γ and TNF-α producing, T-bet+ CD8+ and CD4+ T cells. IL-23 and IL-17 secreting dermal γδ T cells are pathogenic in the imiquimod model, but their cell numbers decreased in the absence of Tregs. Functional experiments demonstrated that myeloid-derived type I Interferon drove the exacerbated inflammation, which was dependent on CD4+ and CD8+ T cells. In conclusion, skin Tregs have a protective role in psoriasis-like inflammation and depletion of Tregs causes disease exacerbation and triggers an altered cytokine profile and cellular infiltrate. These findings assist in our understanding of tissue resident Tregs and how they maintain homeostasis and prevent inflammation in the skin.